Asphalt-based hollow activated carbon microspheres and their manufacturing method, electrode sheet and supercapacitor

JP2025506483AActive Publication Date: 2025-03-11CHINA SHENHUA COAL TO LIQUID & CHEM CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024547468
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-15
Filing Date
2023-02-10
Publication Date
2025-03-11
Estimated Expiration
2043-02-10

AI Technical Summary

Benefits of technology

【0014】 上記の技術的解決手段により、本発明は以下の有益な効果を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025506483000001_ABST
    Figure 2025506483000001_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of electrochemical energy storage material preparation, and discloses asphalt-based hollow activated carbon microspheres and the preparation method thereof, electrode sheet, and supercapacitor. The preparation method of the asphalt-based hollow activated carbon microspheres includes the following steps: (1) mixing low ash asphalt with a solvent to obtain a mixed asphalt solution; (2) subjecting the mixed asphalt solution to spray pyrolysis under an inert atmosphere to obtain hollow carbon microspheres; (3) mixing the hollow carbon microspheres with an activator and activating them to obtain activated carbon; (4) subjecting the activated carbon to acid washing and water washing to remove impurities, and drying to obtain hollow activated carbon microspheres. Such a method has the characteristics of simple process, low preparation cost, and suitable for continuous production. The asphalt-based hollow activated carbon microspheres prepared by the method disclosed herein have high specific surface area, stable performance, environmental friendliness and well-defined hollow structure, and the supercapacitors prepared from such microspheres have high specific capacitance and high cycling capacity retention.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [Technical field] The present invention relates to the technical field of electrochemical energy storage material preparation, and more particularly to the technical field of asphalt-based hollow activated carbon microspheres and their preparation method, electrode sheet and supercapacitor.

[0002] [Background technology] The continuous consumption of fossil energy not only causes a serious energy crisis, but also brings about a series of environmental problems. Therefore, the development of new renewable energy sources, such as solar energy and wind energy, has become the focus of people's research, and its key component, energy storage device, has also made considerable progress. Among many energy storage elements, supercapacitors occupy a unique position in today's energy storage industry due to their characteristics of short charging time, long service life, good temperature characteristics, energy saving and environmental protection.

[0003] Generally, a supercapacitor is composed of an electrode material, a membrane, an electrolyte, and an outer shell. As the core component of the capacitor, the electrode material plays an important role in its performance. Carbon materials are widely used as electrode materials due to their excellent ductility, high chemical stability, and abundant surface functional groups. Among various carbon materials, hollow carbon microspheres not only have excellent electrical conductivity and a very high specific surface area, but also can function as a storage space for electrolyte ions due to their unique hollow structure, thereby effectively shortening the transmission distance between electrolyte ions and micropores and exhibiting a higher reversible specific capacity.

[0004] At present, the commonly used methods for preparing hollow carbon microspheres mainly include the template method, the suspension polymerization method, the hydrothermal method, the spray drying method, and the high-temperature pyrolysis method, of which the spray method is the most promising technical method for industrial production due to its advantages of high speed, high efficiency, mass production, etc.

[0005] CN101541674A discloses a method for preparing mesoporous carbon microspheres with large specific surface area and fine pore size, which includes the following steps: premixing carbon precursor, template agent and solvent, forming a composite of carbon microsphere precursor by spray drying, then carbonizing at high temperature, and finally removing the template to form activated carbon microspheres. Although the principle of such a method is simple, the formation of spheres and distribution of carbonization increase the complexity of the process, and furthermore, the template agent needs to be removed later, and the removal technique may increase the environmental and cost burden, especially for template agents such as certain metal oxides or SiO2. In addition, the specific surface area of ​​the produced activated carbon is low (700 m 2 / g~1300m 2 / g), which cannot meet the requirements as an electrode material for supercapacitors.

[0006] CN109250716A discloses a method for preparing asphalt-based hollow activated carbon, which includes the following steps: uniformly mixing asphalt with a low softening point (30°C-60°C) and asphalt with a high softening point (150°C-360°C), adding to a spray granulator, drying at a suitable temperature of 100°C-220°C, and then carbonizing and activating the mixture without melting to produce hollow activated carbon with a diameter of 0.1mm-2.0mm and a specific surface area of ​​1300m. 2 / g~1600m 2 This method also has problems such as a long non-melting processing time, complicated technical steps, etc., and furthermore, the viscosity of the asphalt itself is high, and even if low-softening point asphalt is added, the fluidity of the whole system still has problems, and it is difficult to completely volatilize the low-softening point asphalt during spraying and form sufficient pores.

[0007] CN106744783A discloses a method for preparing graphitized hollow carbon microspheres, which includes the following steps: using asphalt and additives as raw materials, and preparing graphitized hollow carbon microspheres through mixing, carbonization, acid washing and other techniques, and the specific surface area of ​​the resulting carbon microspheres is greater than 100 m 2 / g~1500m 2 / g, and the average particle size is 0.1 μm-2 μm. Although the manufacturing technology of this method is not complicated, this method still belongs to the scope of preparing hollow carbon sphere structures by hard templates, and in the process, since it involves additives in the form of metal salts, such as metal salts of Fe, Mg, Ca, and Zn, there are still problems with recovering and processing the template, and metal impurity ions tend to remain. These limit the applications of carbon materials, and especially in the electrochemical field, metal impurity ions greatly affect the internal resistance of the material and directly affect the electrochemical performance of the material.

[0008] In summary, although hollow activated carbon microspheres have a wide range of potential applications, there are still some problems, such as the complicated manufacturing technology, the need to introduce a template agent, the tendency to cause environmental pollution, and the low specific surface area of ​​the prepared activated carbons, which cannot meet the requirements of supercapacitor electrode materials.

[0009] Summary of the Invention The object of the present invention is to overcome the problems of the prior art, such as having a complicated hollow activated carbon microsphere manufacturing technology, needing to introduce a template agent, being prone to environmental pollution, and the prepared activated carbon having a low specific surface area, which cannot meet the requirements of supercapacitor electrode materials, and to provide an asphalt-based hollow activated carbon microsphere and its manufacturing method, electrode sheet and supercapacitor, which further has the characteristics of a simple manufacturing process, low manufacturing cost and suitable for continuous production. The asphalt-based hollow activated carbon microsphere prepared by the method disclosed herein has a high specific surface area, stable performance, environmental friendliness and a distinct hollow structure. When applied to a supercapacitor, the resulting capacitor has a high specific capacitance and a high cycle capacity retention rate.

[0010] In order to achieve the above object, the present invention provides, in a first aspect, a method for preparing asphalt-based hollow activated carbon microspheres, the method comprising the steps of: (1) Mix low ash asphalt with a solvent to obtain a mixed asphalt solution; (2) subjecting the mixed asphalt solution to spray pyrolysis under an inert atmosphere to obtain hollow carbon microspheres; (3) mixing the hollow carbon microspheres with an activator and activating them to obtain activated carbon; (4) The activated carbon is subjected to acid washing and water washing to remove impurities, and drying to obtain hollow activated carbon microspheres.

[0011] In a second aspect, the present invention provides asphalt-based hollow activated carbon microspheres prepared by the above method. Such asphalt-based hollow activated carbon microspheres have a particle size of 5 μm to 40 μm and a mass of 1600 μm. 2 / g~2450m 2 Specific surface area of ​​1.8 m / g 3 / g~3.2m 3 / g pore volume.

[0012] In a third aspect, the present invention provides an electrode sheet, the electrode sheet comprising the asphalt-based hollow activated carbon microspheres of the second aspect.

[0013] In a fourth aspect, the present invention provides a supercapacitor, the supercapacitor comprising the electrode sheet according to the third aspect.

[0014] Through the above technical solutions, the present invention can achieve the following beneficial effects:

[0015] (1) In the present invention, the physical property difference between the solvent and asphalt is utilized to prepare hollow carbon microspheres with good sphericity and controllable particle size. When applied to supercapacitors, the hollow structure can provide a temporary storage space for the electrolyte, effectively shortening the transmission distance between the electrolyte ions and the active sites, and thus exhibiting a higher reversible specific capacity.

[0016] (2) In the prior art, hollow carbon microspheres are generally prepared by hard (soft) template method, during which silicon dioxide, metal oxide, silicate, etc. need to be added as template agents, and there are certain problems in processing and recycling the template. In the present invention, a self-template method using asphalt directly as raw material is used, and the hollow structure is directly prepared by utilizing the physical property difference between the asphalt solute and the organic solvent, thereby eliminating the steps of introducing and removing the template, greatly reducing the manufacturing cost and technical complexity, and solving the problem of environmental pollution caused by the removal of the template in the template method.

[0017] (3) Asphalt has an excessively high viscosity and is prone to caulking, which blocks pipelines, when heated at high temperatures for a long period of time, so there has been a major problem with the sustainability of raw material transportation. In the present invention, by adopting an embodiment in which the solvent and asphalt are co-supplied, a hollow structure can be obtained, while on the other hand, the fluidity of the asphalt can be improved and the softening temperature of the mixed solution can be lowered, which prevents blockage of the transportation pipeline and is beneficial for long-term industrial operation.

[0018] (4) In the present invention, asphalt can be directly carbonized and pelletized in a single process, which solves the problems of energy consumption and sphere adhesion caused by long pre-oxidation and carbonization in conventional technologies such as the emulsion method and low-temperature spray method, and greatly improves production efficiency.

[0019]

[0018] BRIEF DESCRIPTION OF THE DRAWINGS FIG. 1 is a SEM photograph of the hollow carbon microspheres obtained in step (2) of Example 1.

[0020] FIG. 2 is the particle size distribution diagram of the asphalt-based hollow carbon microspheres prepared in Example 1.

[0021] Detailed Description The range endpoints and any values ​​disclosed herein are not intended to be limited to the exact ranges or values, but rather should be understood to comprise values ​​close to these ranges or values. For numerical ranges, the range endpoints, range endpoints and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0022] The present invention provides a method for preparing asphalt-based hollow activated carbon microspheres, the method comprising the steps of: (1) Mix low ash asphalt with a solvent to obtain a mixed asphalt solution; (2) subjecting the mixed asphalt solution to spray pyrolysis under an inert atmosphere to obtain hollow carbon microspheres; (3) mixing the hollow carbon microspheres with an activator and activating them to obtain activated carbon; (4) The activated carbon is subjected to acid washing and water washing to remove impurities, and drying to obtain hollow activated carbon microspheres.

[0023] In the present invention, carbon microspheres having a hollow structure are prepared by the combined effect of the difference in physical properties between asphalt and the solvent and the characteristics of the spray pyrolysis process.

[0024] As a result of research, the inventors of the present invention have found that when a mixed asphalt solution is atomized in a high-temperature environment, the evaporation of the organic solvent creates a situation in which the movement rate of the solvent on the surface of the spherical droplets is faster than the diffusion rate of the asphalt, which increases the concentration of asphalt on the droplet surface and causes further solidification and carbonization, thereby obtaining hollow carbon microspheres with good sphericity and controllable particle size.

[0025] The preparation method of asphalt-based hollow activated carbon microspheres provided by the present invention has the characteristics of simple process steps, low preparation cost, suitable for continuous production, etc.

[0026] In the present invention, the mixing conditions in step (1) are not particularly limited as long as they can promote dissolution of the low ash content asphalt. Preferably, the mixing is carried out under conditions including a temperature of 90°C to 300°C and a heating time of 0.5 hours to 2 hours.

[0027] In some embodiments of the present invention, the low ash asphalt is preferably selected from at least one of coal liquefaction asphalt, petroleum asphalt, coal asphalt, coal coke asphalt, synthetic asphalt and natural asphalt. Preferably, the low ash asphalt has an ash content of 1% by weight or less, a metal content of less than 100 ppm by weight, and a softening point of less than 250°C.

[0028] In the present invention, the solvent is not particularly limited as long as it can dissolve the low ash content asphalt. Preferably, the solvent is selected from at least one of coking wash oil, quinoline, pyridine, toluene, xylene, carbon disulfide, tetrahydrofuran, carbon tetrachloride, coal liquefied gas oil, and petroleum middle distillate.

[0029] In some embodiments of the present invention, the mass ratio of the low ash asphalt to the solvent is preferably 1:1 to 5, and more preferably 1:1 to 2. When the above conditions are met, the prepared asphalt-based hollow activated carbon microspheres can have a high specific surface area, stable performance and distinct hollow structure; when applied to a supercapacitor, the specific capacitance and cycle capacity retention of the capacitor can be significantly increased.

[0030] In some embodiments of the present invention, in the step (2), the spray pyrolysis is carried out under conditions including a nozzle hole diameter of 0.5 mm to 2 mm, a nozzle supply pressure of 0.1 MPa to 2.5 MPa, a spray pyrolysis temperature of 550°C to 800°C, a discharge temperature of 550°C to 700°C, and a raw material liquid retention time of 5 to 15 seconds.

[0031] It should be noted that the higher the proportion of asphalt in the mixed asphalt solution, the lower the spray pyrolysis temperature, the larger the nozzle hole diameter, and the higher the spray pressure, the larger the particle size and thinner the sphere wall of the hollow carbon microspheres prepared. The selection of different solvents has a great impact on the viscosity of the mixed asphalt solution, and at the same time, has a certain impact on the particle size. Specifically, corresponding adjustments can be made according to different practical application scenarios.

[0032] In the present invention, the mixing process in the step (3) is not particularly limited as long as it can ensure that the hollow carbon microspheres and the activator are mixed uniformly. Preferably, the mixing process includes a step of pulverizing the hollow carbon microspheres and the activator with a pulverizer to mix them uniformly, where the rotation speed of the pulverizer is 5000 r / min to 25000 r / min.

[0033] In some embodiments of the present invention, preferably, the mass ratio of the hollow carbon microspheres to the activator is 1:0.5-4, preferably 1:1-3.

[0034] In some embodiments of the invention, preferably the activator is selected from at least one of potassium-containing oxides, potassium salts, KOH, alkaline earth metal salts and oxides, H3PO4 and ZnCl2, preferably selected from at least one of KOH, K2CO3, KHCO3, KCl and KMnO4.

[0035] In some embodiments of the present invention, preferably, the activation is carried out under conditions including an activation temperature of 600° C. to 900° C., preferably 700° C. to 800° C.; an activation time of 0.5 hours to 2.5 hours; a heating rate of 1° C. / min to 10° C. / min; and the activation is carried out under an inert atmosphere, preferably nitrogen or argon.

[0036] In some embodiments of the invention, the activation can be performed by direct heating or stepwise heating. Preferably, stepwise heating is adopted. Stepwise heating specifically means heating from room temperature to 500°C, holding this for 0.5 to 1 hour, and then heating to an activation temperature of 600°C to 900°C, preferably 700°C to 800°C. Here, the heating rate is 1°C / min to 10°C / min.

[0037] Through research, the inventors of the present invention have found that the stepwise heating storage method can remove excess water of crystallization in the activator in advance, so that the activation effect is more obvious, the purpose of reducing the amount of activator added is achieved, and the prepared asphalt-based hollow activated carbon microspheres have more stable performance.

[0038] In some embodiments of the present invention, in the step (4), the acid is selected from at least one of hydrochloric acid, nitric acid, and sulfuric acid, and is preferably hydrochloric acid. The acid has a concentration of 0.5 mol / L to 3 mol / L, and preferably 1 mol / L.

[0039] In the present invention, the drying conditions in the step (4) are not particularly limited, and the drying is preferably performed under conditions including a temperature of 80° C. to 120° C. and a drying time of 6 hours to 12 hours.

[0040] In a second aspect, the present invention provides asphalt-based hollow activated carbon microspheres prepared by the above method. Such asphalt-based hollow activated carbon microspheres have a particle size of 5 μm to 40 μm and a mass of 1600 μm. 2 / g~2450m 2 Specific surface area of ​​1.8 m / g 3 / g~3.2m 3 The hollow activated carbon microspheres prepared by the method disclosed herein have a high specific surface area, stable performance, environmental friendliness, and well-defined hollow structure.

[0041] In a third aspect, the present invention provides an electrode sheet comprising the sphalt-based hollow activated carbon microspheres of the second aspect above.

[0042] In a fourth aspect, the present invention provides a supercapacitor comprising the electrode sheet according to the third aspect. The supercapacitor provided by the present invention has a high specific capacitance and a high cycle capacity retention rate.

[0043] The present invention will be described in detail below with reference to examples. Note that all raw materials in the following examples and comparative examples are commercially available unless otherwise specified.

[0044] In order to obtain the pore structure of the prepared sample, a Micromeritics ASAP2020 type specific surface area and porosity analyzer was used to carry out the adsorption and desorption test according to the following procedure: First, the sample was degassed for 12 hours, and then the degassing temperature was controlled at 300°C, and a low-temperature adsorption and desorption test was carried out by program control. The specific surface area of ​​the material was calculated by the BET (Brunauer-Emmett-Teller) model, and the pore volume of the material was calculated by density functional theory (DFT).

[0045] The morphology of the samples is characterized by scanning with a HITACHI FlexSEM1000 II type scanning electron microscope (SEM).

[0046] The particle size distribution of the prepared samples is measured using a Malvern MS2000 type particle size distribution analyzer.

[0047] Example 1 Preparation of asphalt-based hollow activated carbon microspheres: (1) 1 kg of low ash asphalt and 1.5 kg of washing oil were added to a mixing vessel to prepare a mixed asphalt solution with a mass ratio of 1:1.5. The mixed asphalt solution was heated to 180°C (referred to as the "mixing temperature") and mixed at a constant temperature for 0.5 hours. The mixing speed was 100 r / min; the heating rate was 5°C / min; the asphalt used was obtained from the direct coal liquefaction residue extraction and separation process of China Shenhua Coal Chemical Co., Ltd. (i.e., "coal liquefaction asphalt"), with an ash content of less than 0.1% by weight and a softening point of 170°C; the washing oil used had a density of 1.056 g / cm 3 This was a conventional coke washing oil.

[0048] (2) The above 180°C mixed asphalt solution was sprayed into a 750°C spray tower in a nitrogen atmosphere from a 1mm diameter nozzle at a pressure of 0.1MPa (referred to as the "nozzle supply pressure") to subject it to a high-temperature pyrolysis reaction, forming hollow carbon microspheres, and then the solid product was collected in a high-temperature bag dust collector, naturally cooled to room temperature, and the excess oil gas was discharged. The piping between the nozzle and the stirring vessel was kept at 180°C, the nitrogen temperature (or spray pyrolysis temperature) was 750°C, the pressure was 0.08MPa, the discharge temperature was 550°C, and the raw material liquid retention time was 7 seconds.

[0049] (3) 5g of the above hollow carbon microspheres and 10g of KOH (activator) were crushed and mixed uniformly in a high-speed universal grinder, then placed in a tubular furnace protected by nitrogen at 800°C and fired at a constant temperature for 2 hours, and naturally cooled to room temperature to obtain activated carbon microspheres. The rotation speed of the grinder was 24000r / min, the crushing time was 10 seconds, and the tubular furnace was heated in the following steps: from room temperature to 500°C at a heating rate of 10°C / min, the temperature of 500°C was kept for 1 hour, the temperature was raised from 500°C to 800°C at a heating rate of 5°C / min, and the temperature of 800°C (referred to as the "activation temperature") was kept for 2 hours (referred to as the "activation time").

[0050] (4) The activated carbon microspheres were placed in a beaker, and 200 mL of 1 mol / L aqueous hydrochloric acid solution was dropped into it, thoroughly stirred and reacted for 15 minutes, and then filtered. This operation was repeated twice; then, sufficient deionized water was added to the filter residue obtained by acid washing, thoroughly stirred for 15 minutes, and filtered. This operation was repeated three to five times until the pH value of the filtrate was ≒7, and a filter residue was obtained. Furthermore, the filter residue was dried in a blower drying oven at 80°C for 12 hours to obtain asphalt-based hollow activated carbon microspheres.

[0051] The hollow carbon microspheres obtained in step (2) were subjected to SEM examination. Figure 1 shows the SEM image of the hollow carbon microspheres. From Figure 1, it can be seen that the hollow carbon microspheres have a distinct hollow structure.

[0052] The pore structure of the prepared asphalt-based hollow activated carbon microspheres was examined, and the examination results were shown in Table 1.

[0053] The particle size of the prepared asphalt-based hollow activated carbon microspheres was examined. Figure 2 shows the particle size distribution of the prepared asphalt-based hollow activated carbon microspheres. From Figure 2, it can be seen that the particle size of the above asphalt-based hollow activated carbon microspheres is 10 μm to 20 μm.

[0054] Preparation of electrode sheets: The asphalt-based hollow activated carbon microspheres prepared above, acetylene black, and polytetrafluoroethylene (PTFE) (15 wt%) were mixed uniformly in ethanol at a mass ratio of 8:1:1. The mixture was rolled up into a thin plate of uniform thickness using a roller, and the plate was dried in an oven at 80°C for 12 hours. The dried plate was cut into circular sheets using a sheet cutter, and the circular sheets were pressed onto foamed nickel using a press to obtain an electrode sheet.

[0055] Supercapacitor assembly and electrochemical performance testing: Three-electrode test: The above electrode sheet was placed in a three-port electrolytic cell, and a 6M KOH solution was used as the electrolyte, a platinum electrode was used as the counter electrode, and a Hg / HgO electrode was used as the reference electrode. A charge-discharge test was performed using a Metrohm Nova Autolab electrochemical workstation at a voltage range of 0-1 V, a current density of 1 A / g, and a test temperature of 25° C. The results of the electrochemical test are shown in Table 1.

[0056] Two-electrode test: The above electrode sheet was assembled into a button battery in the form of battery case-electrode sheet-membrane (polypropylene)-6M KOH-electrode sheet-battery case, and then the rate and long cycle performance of the button battery were tested in the Wuhan Land Battery Test System at a voltage range of 0-1V, a current density of 1A / g, 10,000 long cycle charge / discharge cycles, and a test temperature of 25°C. The results of the electrochemical test are shown in Table 1.

[0057] [Examples 2 to 12 and Comparative Examples 1 to 3] Asphalt-based hollow activated carbon microspheres were prepared in the same manner as in Example 1, except that the parameters shown in Table 1 were adjusted.

[0058] The pore structure and particle size of the prepared asphalt-based hollow activated carbon microspheres were examined, and the examination results are shown in Table 1.

[0059] An electrode sheet was prepared according to the method of Example 1, and a supercapacitor was assembled and electrochemical performance tested according to Example 1. The test results are shown in Table 1.

[0060] [Table 1-1]

[0061] [Table 1-2]

[0062] From the results in Table 1, the particle size of the asphalt-based hollow activated carbon microspheres prepared by the method disclosed herein is 5 μm to 40 μm, and the specific surface area is 1600 m 2 / g~2450m 2 / g and the pore volume is 1.8 m 3 / g~3.2m 3 It can be seen that the specific surface area and pore volume of the asphalt-based hollow activated carbon microspheres of Examples 1 to 12 were obviously higher than those of Comparative Examples 1 to 3. When the asphalt-based hollow activated carbon microspheres prepared according to the present invention were used in a supercapacitor, the specific capacitance of the supercapacitor was obviously higher than that of the Comparative Examples.

[0063] In conclusion, the asphalt-based hollow activated carbon microspheres prepared by the technical solution of the present invention have a large specific surface area, uniform particle size, and stable performance. Furthermore, the preparation method has the characteristics of simple process, low preparation cost, and suitable for continuous production. When the prepared asphalt-based hollow activated carbon microspheres are used in a supercapacitor, the supercapacitor has a high specific capacitance and a high cycle capacity retention rate.

[0064] The above are preferred embodiments of the present invention, but are not intended to limit the present invention. Within the scope of the technical concept of the present invention, the technical solutions of the present invention can be made to many simple modifications consisting of combinations of various technical features in any other suitable manner. These simple modifications and combinations are also considered as the contents disclosed by the present invention and belong to the protection scope of the present invention. [Brief description of the drawings]

[0065] [Figure 1] FIG. 1 is a SEM photograph of the hollow carbon microspheres obtained in step (2) of Example 1. [Diagram 2] FIG. 2 is the particle size distribution diagram of the asphalt-based hollow carbon microspheres prepared in Example 1.

Claims

1. 1. A method for preparing asphalt-based hollow activated carbon microspheres, comprising the steps of: (1) mixing low ash content asphalt with a solvent to obtain a mixed asphalt solution; (2) subjecting the mixed asphalt solution to spray pyrolysis under an inert atmosphere to obtain hollow carbon microspheres; (3) mixing the hollow carbon microspheres with an activator and activating them to obtain activated carbon; (4) The activated carbon is subjected to acid washing and water washing to remove impurities, and drying to obtain hollow activated carbon microspheres.

2. 2. The method of claim 1 , In the step (1), the mixing is carried out under conditions including a temperature of 90° C. to 300° C. and a heating time of 0.5 hours to 2 hours; Preferably, the low ash asphalt is selected from at least one of coal liquefaction asphalt, petroleum asphalt, coal asphalt, coal coke asphalt, synthetic asphalt and natural asphalt; Preferably, the low ash asphalt has an ash content of 1% by weight or less, a metal content of less than 100 ppm by weight, and a softening point of less than 250°C; Preferably, the solvent is selected from at least one of coking wash oil, quinoline, pyridine, toluene, xylene, carbon disulfide, tetrahydrofuran, carbon tetrachloride, coal liquid gas oil and petroleum middle distillates; Preferably, the mass ratio of said low ash asphalt to said solvent is 1:1-5, preferably 1:1-2.

3. 2. The method of claim 1 , In the step (2), the spray pyrolysis is carried out under conditions including a nozzle hole diameter of 0.5 mm to 2 mm, a nozzle supply pressure of 0.1 MPa to 2.5 MPa, a spray pyrolysis temperature of 550°C to 800°C, and a discharge temperature of 550°C to 700°C.

4. 2. The method of claim 1 , The mass ratio of the hollow carbon microspheres to the activator is 1:0.5-4, preferably 1:1-3; Preferably, the activator is an oxide containing potassium, a potassium salt, KOH, an alkaline earth metal salt and an alkaline earth metal oxide, H 3 P.O. 4 and ZnCl 2 is selected from at least one of Preferably, KOH, K 2 CO 3 , KHCO 3 , KCl and KMnO 4 The method is selected from at least one of the following:

5. 2. The method of claim 1 , In the step (3), the activation is carried out under conditions including an activation temperature of 600° C. to 900° C., preferably 700° C. to 800° C.; an activation time of 0.5 hours to 2.5 hours; and a heating rate of 1° C. / min to 10° C. / min; A process wherein said activation is carried out under an inert atmosphere, preferably under nitrogen or argon.

6. 2. The method of claim 1 , In the step (4), the acid is selected from at least one of hydrochloric acid, nitric acid, and sulfuric acid, preferably hydrochloric acid; Preferably, the concentration of the acid is between 0.5 mol / L and 3 mol / L; Preferably, the drying is carried out under conditions comprising a temperature of from 80° C. to 120° C. for a time period of from 6 hours to 12 hours.

7. Asphalt-based hollow activated carbon microspheres prepared by the method of any one of claims 1 to 6.

8. 8. The asphalt-based hollow activated carbon microspheres of claim 7, The asphalt-based hollow activated carbon microspheres have a particle size of 5 μm to 40 μm and a diameter of 1600 mm. 2 / g~2450m 2 Specific surface area of ​​1.8 m 3 / g to 3.2 m 3 Asphalt-based hollow activated carbon microspheres with a pore volume of 1000 / g.

9. 9. An electrode sheet comprising the asphalt-based hollow activated carbon microspheres of claim 7 or 8.

10. A supercapacitor comprising the electrode sheet of claim 9.

11. 11. The supercapacitor of claim 10, wherein the supercapacitor has a specific capacitance of 170 F / g to 270 F / g.

Citation Information

Patent Citations

  • Preparation method of asphalt-base hollow spherical active carbon

    CN109250716A

  • Preparation of asphalt-based carbon microspheres and application of asphalt-based carbon microspheres in supercapacitor electrode

    CN112875700A

  • Preparation method of spherical activated carbon, spherical activated carbon and preparation device of spherical activated carbon

    CN113716561A

  • Method for producing porous carbon particle

    JP2018177564A

  • Method for producing porous carbon particles, and porous carbon particles

    WO2018186003A1